2023
DOI: 10.3389/fpsyg.2023.1181832
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 pandemic on major depressive disorder in acute psychiatric inpatients

Abstract: IntroductionThe spread of the coronavirus disease 2019 (COVID-19) pandemic and the subsequent restrictions significantly affected mental health, especially major depressive disorder (MDD) whose incidence increased by 27.6% in 2020, after the COVID-19 outbreak. Few studies focused on the impact of the pandemic on the clinical characteristics of outpatients with MDD and even fewer on inpatients admitted for a major depressive episode (MDE). We aimed to compare the characteristics of MDD of two groups of patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 58 publications
0
5
0
4
Order By: Relevance
“…Nevertheless, in Italy, a country heavily affected by the pandemic, suicide attempts among psychiatric inpatients increased during 2020 pointing toward a worsening of psychiatric conditions ( 49 ). In line, Brasso et al ( 50 ) demonstrated that MDD patients admitted to hospital after the lockdown suffered from a higher rate of suicidal ideation and more psychotic features. Furthermore, a higher antidepressant dosage and more augmentation therapy strategies were applied in those patients.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Nevertheless, in Italy, a country heavily affected by the pandemic, suicide attempts among psychiatric inpatients increased during 2020 pointing toward a worsening of psychiatric conditions ( 49 ). In line, Brasso et al ( 50 ) demonstrated that MDD patients admitted to hospital after the lockdown suffered from a higher rate of suicidal ideation and more psychotic features. Furthermore, a higher antidepressant dosage and more augmentation therapy strategies were applied in those patients.…”
Section: Discussionmentioning
confidence: 64%
“…Furthermore, a higher antidepressant dosage and more augmentation therapy strategies were applied in those patients. These findings highlight the impact the pandemic had on depressive symptom severity ( 50 ). Also, in Japan a decline in suicide rates during the first wave was reported for children as well as for adults ( 51 , 52 ), followed by a substantial increase in suicides by adults from July to October 2020 ( 52 ).…”
Section: Discussionmentioning
confidence: 71%
“…The COVID-19 pandemic significantly contributed to an increase in the rate of depressive episodes within MDD [ 47 ]. In our study, the criteria for defining the PCD group corresponded to the clinical criteria for diagnosing a depressive episode within MDD according to ICD-10.…”
Section: Discussionmentioning
confidence: 99%
“…Una mayor participación paterna [OR 1,5 (1,09, 2,07)] se asoció con mayor retraso frente a las normas internacionales. La maternidad adolescente [OR 4,09 (1,40,11,87)] disminuyó el desarrollo de los niños frente a sus pares. El compromiso de los adultos no parentales redujo las probabilidades de retraso para ambos resultados [OR (95 % IC = 0,76 (0,63, 0,91) y 0,27 (0,15, 0,48)] respectivamente.…”
Section: Usa Originalunclassified
“…Varias herramientas tecnológicas son utilizadas en la práctica clínica e independientemente de sus limitaciones, lo cual podría demostrar su eficacia para el control de la composición corporal. 24 Brasso C, Cisotto M, Del Favero E, Giordano B, Villari V, Rocca P. (2023) (40) China Original Comparar las características del trastorno depresivo mayor de dos grupos de pacientes ingresados antes y después del brote pandémico de COVID-19 e investigar las variables relacionadas con hospitalizaciones En 757 niños y adolescentes de 8 a 18 años de edad, hospitalizados con trastorno depresivo mayor, la evaluación antropométrica evidenció: bajo peso 8,2 %, sobrepeso 15,5 % y obesidad 10,4 %. Con respecto a ideas suicidas e intentos suicidas, la prevalencia de ideas suicidas en pacientes con bajo peso fue de 22,6 %, sobrepeso 20,5 % y obesidad 19,0 %, mientras que en intentos de suicidio en pacientes con bajo peso fue de 8,1 %, sobrepeso 12,0 % y obesidad 13,9 %, evidenciando que el IMC se correlacionó positivamente con la edad de la primera hospitalización, duración total de la enfermedad y número de hospitalizaciones por dicho trastorno.…”
Section: Polonia Originalunclassified